Politik Hukum Otonomi Daerah Dalam Mewujudkan Tata Kelola Pemerintahan Yang Baik di Bidang Kesehatan - Azlan Thamrin (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2019)
The implementation of regional autonomy provides the opportunity for local governments to create progress in many aspects, including in the field of health. The research site is in Bone Regency.The research aimed (1) to investigate and understand the legal politics of the regional autonomy in realizing the good governance in health sector; (2) to investigate and understand the application of the good governance principles in the implementation of the administration affairs of the government.The research was an empirical legal research which usually called a socio-legal research. The research was conducted in the Regional Government of Bone Regency. The research was qualitative and was supported legal materials. The data were analyzed using the descriptive and qualitative content analysis.The research result indicated that (1) the legal policy of the regional autonomy in the realization of the good governance in health sector in Bone Regency was based on right of the health protection; that the government must give the right to every citizen, and the local government of Bone Regency should be involved in the health protection based on the principles of autonomy. That between the local government and the central government there should be a division of authority in order to avoid the overlapping authority. Therefore, the formats of regulatory, funding, and implementation are needed in order that the implementation of the health service could reach the community directly. (2) The application of a good governance in the implementation of the government affairs in the health sector in Bone Regency is measured based on: the community access to the information about the government coordination, the community trust in the government institutions (particularly in the health sector), the consistency of the local government of Bone Regency in enforcing the law when executing the government, and the involvement of the non-governmental elements in the policy making (particularly in the health sector). All these effect satisfaction level of the authority implementation of the local government of Bone regency in the health sector, 20 out of 40 respondents has given their good evaluation in the health sector; that the health service in the regency has been running well.